High Incidence of Hepatitis B Virus Infection in Hemodialysis Patients at Sanglah General Hospital and It’s Risk Factors - Cokorda Agung Wahyu Purnamasidhi; I Ketut Mariadi; I Dewa Nyoman Wibawa; Yenny Kandarini (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Background: Patients receiving maintenance hemodialysis (HD) are at higher risk for Hepatitis B Virus (HBV) infections than in general population. Strict infection control is essential to prevent nosocomial transmission. We aimed to investigate the incidence of HBV infection in the HD population in Sanglah General Hospital as well as risk factors acquired HBV infection.Method: All adult patients receiving maintenance HD (n=267) in 3 dialysis units at Sanglah Hospital were studied between March to June 2016. In this study, medical record of patients on maintenance hemodialysis were reviewed and the patients were interviewed by the researchers to collect data regarding the serology status of these patients before and during HD, and potential risk factors which could be associated with HBV acquisition.Results: Participant mean age was 54.07 ± 0.80 years and 154 (57.7%) were male.We found 21 patients (7.8%) were sero-positive for HBV (HBsAg positive) with mean titer was 9.26±1.85. Of the sero-positive patients,1 patient (4.8%) were known to be infected before the initiation of HD and 20 patients (95.2%) were infected during HD. Incidence of HBV infection during  HD was 7.5% (20/266). Sero-positive patients were younger with mean age was 51.81±2.76 years, had longer time on dialysis and had previous blood transfusions. Risk factors, which significant associated with hepatitis B infection were history of transfusion (p0.01; OR: 2.49; 95%CI: 1.29-8.18) and duration of hemodialysis (p 0.01; OR: 1.07; 95% CI: 1.03-3.74).Conclusion: Patients on maintenance HD in Sanglah General Hospital have a high incidence of HBV infection. The factors associated with HBV infection are highly suggestive of nosocomial transmission within HD units. History of transfusion and duration of hemodialysis were significant risk factors for HBV infection in patients receiving maintenance HD.